Identifying Functional Grammar Competence: A Study of Students’ Email Writing at English for Correspondence Class - Siska Amelia Maldin; Andri Wibowo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research to identify the lexicogrammatical complexification level of the subjects’ spoken and written narratives (low, moderate, or high?); and to find out whether there is any difference as for the level of lexicogrammatical complexification between the subjects’ spoken and written narratives. The sample of the research is for Portuguese EFL-students who were taking up the Letras undergraduate program at Universidade Estadual do Ceará – UECE and Universidade Federal do Ceará - UFC. The research is done in descriptive one. The result of the research shows that both students’ competence in functional grammar is viewed very high, in which 87.61% for the spoken medium and 94.14% for the written one, and together – 90.72% of all ranking clauses. Basically, the previous research is focused on the same object with this research that is analyzing students’ competence. Unlike the previous one, this research focuses on the students’ competence in functional grammar in analyzing clauses.